Yá sgóonwáan adátx'i neildáxh kha sgóondáxh hasdu eexh dasheeyí, kei kghak’é! Mamawiohpikihawasowin akwa awasisak kisaspin wecihawak wikiwahk akwa kiskinwahamakiwikamikohk kita mithopathin! Supporting First Nations Student Academic Success Through Improved Educator Efficacy - Stoneman, Tammy H (Scholarship@Western, 2023)
Fifty years ago, Together Today for Our Children Tomorrow (1973) stated that Tawaw Education (pseudonym) has been failing to meet the academic needs of First Nations students from K-12. This ongoing issue is highlighted by both the Office of the Auditor General’s Reports (2009; 2019) and Yee’s (2021) Review of Inclusive and Special Education Report. This Organizational Improvement Plan (OIP) addresses the ongoing education issues First Nations people have endured for many years and provides guidance to support improved educator efficacy throughout the system. An Indigenous leadership approach is used to ensure authenticity to this work, highlighting the importance of focusing on community interests and confirming this work benefits everyone. There is focus on creating an inclusive system reflective of First Nations ways of knowing, doing, and being. This improvement plan presents a collaborative approach outlining the journey toward theory and practice necessary to ensure the well-being of First Nations learners and providing a more equitable education system. This initiative to integrate First Nations ways of knowing, doing, and being into everyday planning, teaching, and learning aligns with Tawaw Education’s vision. As communicated in the plan for change, learners and educators are at the centre of a powerful vision for a more inclusive, equitable, and flourishing learning environment at Tawaw Education. Supporting First Nations learners in feeling a sense of belonging in the education system requires culturally relevant curriculum, pedagogy, and assessments reflective of First Nations ways of knowing, doing, and being. Tawaw Education is taking promising steps toward decolonizing possibilities within the organization.